(untitled) (Plant Tissue Culture and Biotechnology, 2009)
Green compact nodular callus was observed within three weeks from nodal segments of a perennial medicinal herb Scoparia dulcis L. on MS basal medium supplemented with 1.5 mg/l BAP + 0.2 mg/I NAA. The callus produced large number of shoots when subcultured on MS with 0.5 mg/l BAP + 0.1 mg/l NAA. In vitro raised shoots rooted on half strength of MS with 1.0 mg/l IBA + 1.0 mg/l NAA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for seven days before transplanting in pots where plantlets were reared for three weeks. The survival rate of plantlets was found to be 85%. Regenerated plants were morphologically uniform having normal leaf shape and growth. Key words: Scoparia dulcis, Medicinal plant, Shoot proliferation, Acclimatization D.O.I. 10.3329/ptcb.v18i1.3268 Plant Tissue Cult. & Biotech. 18(1): 75-83, 2008 (June)